Evaluation of the state of knowledge on hormone replacement therapy among climacteric women in the Lublin Voivodeship (Poland) - Orlicz-Szczęsna, Grażyna; Budzyński, Daniel; Łopucki, Maciej; Grafka, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2012)
The goal of this study was to evaluate the level of knowledge on hormone replacement therapy (HRT) among climacteric women in the Lublin Voivodeship and the factors affecting this level of knowledge. HRT is a system of medical treatment offered to women experiencing a difficult period in their lives, which has become widely used in recent years. The medical literature cites many positive aspects of such therapy during the climacteric period. It should be noted, however, that the list of contraindications for HTR due to the adverse effects of the treatment is still being expanded.